2020
DOI: 10.1017/qua.2020.70
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution of Pacific cod (Gadus macrocephalus) in the North Pacific Ocean over 6 millennia

Abstract: In this paper, we compile estimates of cod size distributions based on zooarchaeological data and contemporary length-frequency data to look at variability in size composition through time across the North Pacific, from the northern Kuril Islands through the Aleutian Islands to southeast Alaska. The results suggest that a strong longitudinal trend in cod size has remained consistent over time, with the largest cod found to the west. We find that five of nine sites show that overall cod length and distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Furthermore, recent studies have reported that body size of various organisms has declined within territorial and aquatic ecosystems (Gardner et al, 2011; Sheridan & Bickford, 2011) including many fish species (Audzijonyte et al, 2020; Baudron et al, 2014; McQueen & Marshall, 2017; Oke et al, 2020) under global warming. In addition, fishing can also lead to declining fish size (Hollins et al, 2018; Link & Watson, 2019; West et al, 2020), contributing to the varying size structure observed in this study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, recent studies have reported that body size of various organisms has declined within territorial and aquatic ecosystems (Gardner et al, 2011; Sheridan & Bickford, 2011) including many fish species (Audzijonyte et al, 2020; Baudron et al, 2014; McQueen & Marshall, 2017; Oke et al, 2020) under global warming. In addition, fishing can also lead to declining fish size (Hollins et al, 2018; Link & Watson, 2019; West et al, 2020), contributing to the varying size structure observed in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Annual centroids (mean ± standard deviation) of each size class of sablefish (cm) in the WGOA in warm (red), cold (blue) and medium (dark grey) years based on bottom temperature (See details about warm/cold/medium years in Li et al, 2019). The cold year of 1999 and warm year of 2015 were identified as '99' and '15' respectively. fishing can also lead to declining fish size (Hollins et al, 2018;Link & Watson, 2019;West et al, 2020), contributing to the varying size structure observed in this study.…”
Section: F I G U R Ementioning
confidence: 89%
“…Formed as a working groups within the Ecosystem Studies of Subarctic and Arctic Seas (ESSAS: ) regional program, PESAS provides a context for the sharing and integration of paleo-research on atmospheric, oceanographic, marine-ecological, and human histories over time scales of millennia to centuries. PESAS embraces research spanning the last 20,000 years, from the last glacial maximum and deglacial period, when people first settled some high-latitude maritime regions (e.g., Fitzhugh 2022), to recent centuries, when massive commercial fisheries became ubiquitous and extraction came to threaten marine ecosystems globally (Pauly et al, 1998; Jackson et al, 2001, Holm et al, 2019 [this issue], West et al, 2020 [this issue]).…”
Section: What Is Pesas?mentioning
confidence: 99%
“…Pacific and Atlantic cod provide another productive pairing. Catherine West et al (2020) compare harvested Pacific cod size data from 6000 years of archaeological sites and modern commercial long-line fisheries around the North Pacific Rim (Kuril Islands to Southeast Alaska). Finding few significant differences between pre-commercial and commercial catch records, they argue that neither pre-industrial harvests nor long-term climate change had measurable effects on fish population structures (i.e., no evidence of "fishing down the food chain" with possible exception of sites in the Western Gulf of Alaska where commercial fishing had its earliest start).…”
Section: This Special Issuementioning
confidence: 99%
“…Collaborations, initiated through the Paleoecology of Subarctic and Arctic Seas (PESAS) working group that inspired this special issue, have started assembling relevant evidence (see West et al, 2020 and Nagashima et al, 2021, in this issue). This coordinated research program promises to open new understanding of the paleoecology of the North Pacific and to extend the dynamic baselines available to contemporary ecologists, managers, and planners.…”
Section: Introductionmentioning
confidence: 99%